2013
DOI: 10.7196/samj.6514
|View full text |Cite
|
Sign up to set email alerts
|

Age-specific prevalence of cervical human papillomavirus infection and cytological abnormalities in women in Gauteng Province

Abstract: Background. Women accessing the public health system in Gauteng province, South Africa are largely unscreened for cervical cancer and have a high background prevalence of human immunodeficiency virus (HIV) infection. Objectives. This cross-sectional study describes the age-specific prevalence of human papillomavirus (HPV) infection and cytological abnormalities among this urban and peri-urban population. Method. Over the period March 2009 -September 2011, 1 524 women attending public sector primary healthcare … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
65
5
3

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 56 publications
(80 citation statements)
references
References 31 publications
(60 reference statements)
6
65
5
3
Order By: Relevance
“…DNA was extracted from the tampon specimens and tested using Roche linear array for HPV DNA testing as described previously. [6] Parents and guardians of girls aged 9 years and older in grades 4 -7 were invited to provide consent, and all girls were requested to provide consent for HPV vaccination. The vaccine was administered per protocol by a team of registered nurses during school hours.…”
mentioning
confidence: 99%
“…DNA was extracted from the tampon specimens and tested using Roche linear array for HPV DNA testing as described previously. [6] Parents and guardians of girls aged 9 years and older in grades 4 -7 were invited to provide consent, and all girls were requested to provide consent for HPV vaccination. The vaccine was administered per protocol by a team of registered nurses during school hours.…”
mentioning
confidence: 99%
“…17 This trend was clearly not present in this study population, and was also reported by Richter, Becker, Horton and Dreyer. 6 Multiple factors may be responsible for why the trend is for HPV infections to persist, rather than to clear. These may include poor herd immunity against HPV, partly because of high HIV infection rates and sexual behaviour patterns.…”
Section: Discussionmentioning
confidence: 99%
“…It is expected that mortality from cervical cancer in these countries can be lowered with any screening test, provided that the necessary coverage, appropriate screening interval, as well as treatment and follow-up of screen-positive individuals can be achieved. 6 To date, the logistical challenges of a speculum and cytologybased screening programme have prevented effective implementation in most developing environments, necessitating the urgent investigation of alternatives.…”
Section: Introductionmentioning
confidence: 99%
“…The high burden of disease demonstrated in this study underlines the importance and urgency of HPV vaccination and screening in SA, and indicates a high expected return on investment. [9] and in the general South African population (dashed lines), as described by Richter et al [8] and unpublished data from the University of Pretoria Gynaecological Oncology Unit (2011). Th e fi gure shows trends and prevalence relative to each other rather than the absolute prevalence, so there is no vertical axis.…”
Section: Fig 1 the History Of Cervical Cancer Prevention And Human mentioning
confidence: 99%
“…[8] This study, performed among women attending public sector primary healthcare clinics in the Tshwane area of Gauteng, describes the highest prevalence of hrHPV ever reported in an unselected screening population (Fig. 3).…”
Section: Fig 1 the History Of Cervical Cancer Prevention And Human mentioning
confidence: 99%